Evaluation of Serum RANKL Level in Acute Coronary Syndrome - Naji, Ali A.; Abbas,, Ahmed A.; Hashem, Rafid B. (AL-Kindy College Medical Journal, 2014)
Background: Acute coronary syndrome (ACS) is a common disease, and a major determinant of morbidity and mortality in all races. The pleiotropic effects of the receptor activator of nuclear factor-kappa B ligand (RANKL) such as modulation of cell survival, mineralization and inflammation, make it an interesting candidate mediator in the progression and destabilization of atherosclerotic lesions.Objectives: This study was performed to investigate the role of RANKL in the pathogenesis of ACS.Methods: The levels of RANKL were measured by ELISA method in sera of 60 ACS patients, 31 patients with unstable angina (UA) and 29 patients with myocardial infarction (MI) in comparison with 20 apparently healthy controls.Results: Current data indicated that there was a decrease in the median serum level of RANKL but statistically not significant (p>0.05)in ACS patients as compared with a healthy control group.Conclusion: Current study revealed a low RANKL serum level but statistically not significant in ACS patients in addition there were no significant differences in median serum levels of RANKL in ACS patients according to gender type, family history, smoking habit and troponin enzyme